ANALISIS PENGARUH ASSETS DAN MANAJEMEN INVENTORY TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG LISTING DI BURSA EFEK INDONESIA 2010 - 2012 - Windasari Rachmawati; Vinsensia Retno Widi Wisayang (Jurnal Ekonomi dan Bisnis, 2018)
This research aims to learn the effect of the values of the quick ratio, turnover asset, return on aset, and inventory turnover toward net profit before taxes in the food and beverage indusry in Jakarta Stock Exchange (Indonesia) in 2012 - 2013. The approach used is qualitative approach with multiple regression. Based on the analysis described previously, it can be concluded that from the independent variable of turnoverasset, retunt on assets and inventory turnover partially have positive and significant impact on Ebit of Profit. this proves the previous studies that management of assets and inventoy affect earning before tax (EBIT). From the analysis ATR, ROA, and ITO have effects on Ebit or Profit. Som the employers of company are advised to keep ATR, ROA and ITR to remain high in order to get higher profits. Keywords : assets, stocks, earnings before tax